Gambaran Tingkat Stres Berdasarkan Stressor Mahasiswa Baru Fakultas Kedokteran Universitas Bosowa Selama Perkuliahan Daring - Andi Lolo, Gandy Patandung; Thamrin, Rahmawati; Hasbullah, Ayu Ameliyah (Fakultas Kedokteran Universitas Bosowa, 2025)
Stress can be interpreted as a non-specific response to emotional disturbances/changes caused by stimulus or pressure (stimulus stressor). Stress in medical students is a phenomenon that can be found in various parts of the world. The prevalence of stress in the world is quite high with various stressors that can affect stress levels in medical students. This research is quantitative descriptive. This research was conducted at the Faculty of Medicine, University of Bosowa in December 2022. The research subjects were students of the Faculty of Medicine, University of Bosowa Class of 2020 and Class of 2021. The sampling technique used was stratified random sampling. Data collection using the Medical Student Stressor Questionnare (MSSQ). Based on the results of research based on the degree of stress, it was found that the teaching and learning process with 51 respondents (33.5%) with moderate stress levels, academic with 49 respondents (32.5%) with moderate stress levels, activities with 49 respondents (32.2%) with moderate stress level, social with 44 respondents (29%) with moderate stress level, motivation with 69 respondents (45.3%) with no stress level at all, intrapersonal and interpersonal with 44 respondents (28.9%) with no stress level stress at all. Based on this research, it was found that what became a stressor for students was the Teaching and Learning Process as the Highest Stressor, followed by Academic, Activity, and Social. Meanwhile, Motivation, Intrapersonal and Interpersonal are not stressors for students of the Faculty of Medicine, University of Bosowa Class of 2020 and Class of 2021.